Legal Review of Legal Protection of People with Mental Disorders (ODGJ) Against Medical Actions based on Human Rights Principles - Maghfiroh, Lulu; Yulianto, Yulianto (Formosa Journal of Applied Sciences, 2024)
Every international human rights convention is based on the same principles that underlie health care. These principles include the following three fundamental ideas: equality, non-discrimination, and government obligations. Everyone has a fundamental right to mental health care, including those who are sick (ODGJ). Government funding is available for mental health institutions, mental health professionals, and mental health equipment so that ODGJ have equal access to treatment. This type of research is known as normative legal research, which analyzes and investigates the norms, doctrines, or principles of legal science by discussing legal issues and attempting to determine the basic concepts of certain legal events, relationships, rights, and legal entities in codified and structured law. A conceptual and legislative approach was taken in this study.